2021
DOI: 10.1038/s41421-021-00271-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of pancreatic ductal adenocarcinoma identifies a novel fibroblast subtype associated with poor prognosis but better immunotherapy response

Abstract: The current pathological and molecular classification of pancreatic ductal adenocarcinoma (PDAC) provides limited guidance for treatment options, especially for immunotherapy. Cancer-associated fibroblasts (CAFs) are major players of desmoplastic stroma in PDAC, modulating tumor progression and therapeutic response. Using single-cell RNA sequencing, we explored the intertumoral heterogeneity among PDAC patients with different degrees of desmoplasia. We found substantial intertumoral heterogeneity in CAFs, duct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
137
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(144 citation statements)
references
References 64 publications
6
137
1
Order By: Relevance
“…It was found that pancreatic ductal adenocarcinoma patients with abundant MeCAFs had a higher risk of metastasis but had a significantly better response to immunotherapy. 136 These results indicate that abnormal glycolysis directly or indirectly affects tumor metastasis. CAFs up‐regulate carnitine palmitoyltransferase 1A (CPT1A) to cause reduction of fatty acid oxidation, leading to peritoneal metastasis of colorectal cancer.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 85%
See 1 more Smart Citation
“…It was found that pancreatic ductal adenocarcinoma patients with abundant MeCAFs had a higher risk of metastasis but had a significantly better response to immunotherapy. 136 These results indicate that abnormal glycolysis directly or indirectly affects tumor metastasis. CAFs up‐regulate carnitine palmitoyltransferase 1A (CPT1A) to cause reduction of fatty acid oxidation, leading to peritoneal metastasis of colorectal cancer.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 85%
“…analyzed CAFs by single‐cell sequencing combined with RNA‐sequence and divided CAFs into four types. 136 One of the subtypes has high glycolytic activity and is termed MeCAFs. It was found that pancreatic ductal adenocarcinoma patients with abundant MeCAFs had a higher risk of metastasis but had a significantly better response to immunotherapy.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%
“…However, in this study, we accurately determined the metabolic transformations that occur in CAFs. Previously, molecular analyses have revealed changes in metabolic genes expressed in CAFs [34][35][36]. These results suggested that CAFs within tumors have an active glycolytic metabolism.…”
Section: Metabolic Transformation In Cafsmentioning
confidence: 90%
“…However, in this study, we accurately determined the metabolic transformations that occur in CAFs. Previously, molecular analyses have revealed changes in metabolic genes expressed in CAFs [33][34][35]. These results suggested that CAFs within tumors have an active glycolytic metabolism.…”
Section: Metabolic Transformation In Cafsmentioning
confidence: 90%